2004
DOI: 10.1016/j.jbtep.2004.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive disorder and the paradoxical effects of perseverative behaviour on experienced uncertainty

Abstract: Patients suffering from Obsessive-compulsive disorder (OCD) tend to check repeatedly and after checking episodes they tend to be uncertain about their memory for checked events. It seems plausible that memory distrust motivates checking, but why checking is repeated and why one check is not enough to reassure the patient is uncertain.To study this, an interactive computer animation displaying light bulbs or gas rings was developed and healthy participants were asked to engage in repeated checking. In five sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 15 publications
7
60
0
3
Order By: Relevance
“…In addition to the large declines in confidence, vividness, and detail, these more recent studies also found small declines in memory accuracy. Van den Hout and Kindt (2004) argued that the conditions of high familiarity, such as those produced by the ''relevant checking'' condition in their study, inhibited processing of the perceptual features of a stimulus which in turn decreased the vividness and detail of later recollections, and subsequently deflated the confidence in that recollection.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition to the large declines in confidence, vividness, and detail, these more recent studies also found small declines in memory accuracy. Van den Hout and Kindt (2004) argued that the conditions of high familiarity, such as those produced by the ''relevant checking'' condition in their study, inhibited processing of the perceptual features of a stimulus which in turn decreased the vividness and detail of later recollections, and subsequently deflated the confidence in that recollection.…”
Section: Introductionmentioning
confidence: 92%
“…Recent research suggests that the declines in memory confidence following repeated checking, at least in non-clinical samples, are larger than the changes in memory accuracy that have been observed (Van den Hout & Kindt, 2004;Coles, Radomsky, & Horng, 2006;Radomsky, Gilchrist, & Dussault, 2006) and that decreases in memory confidence appear to be most salient under conditions of high responsibility (Radomsky et al, 2001). It may be that compulsive checkers do not have a worse memory than others, but rather are less confident in their memory.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Son olarak, ilgili kontrol grubundaki katılımcılar diğer gruba oranla ocakların tam olarak kapalı olup olmadığıyla ilgili soruya anlamlı olarak daha az emin bir şekilde yanıt vermişlerdir. Bu değerlendirme "sonuçtaki güven" (outcome confidence) olarak isimlendirilmiş-tir (Ashbaugh ve Radomsky 2007;van den Hout ve Kindt 2003a, 2003b, 2004, Radomsky ve ark. 2006).…”
Section: Introductionunclassified
“…Başka türlü ifade edilecek olursa, bu yazarlar dış dünyadan gelen verileri kaydetme esnasında algısal (perceptual) düzeyde işlemlemenin anlamsal (semantic) tipteki işlemlemeye doğru dönüştüğünü/değiştiğini önermişlerdir (Tulving 1985). Böylelikle deneydeki katılımcılar bahsedilen hipoteze göre son kontrol seansında özgül olarak hatırlama-dan genel manada bilmeye geçiş yapmışlardır (van den Hout ve Kindt 2004, Johnston ve Hawley 1994, Tulving 1985. İddia takip edildiğinde, bu sürecin sonunda hafızanın canlılık ve detayı azalır.…”
Section: Introductionunclassified